Effect of a Selective Inhibitor of Secretory Phospholipase A2, S-5920/LY315920Na, on Experimental Acute Pancreatitis in Rats - Yasuhiko Tomita; Kenji Kuwabara; Shingo Furue; Kazushige Tanaka; Katsutoshi Yamada; Masahiko Ueno; Takashi Ono; Toshiyuki Maruyama; Tetsuo Ajiki; Hirohiko Onoyama; Masahiro Yamamoto; Yozo Hori (Elsevier, 2004)
We investigated the efficacy of a potent inhibitor of secretory phospholipase A2 (sPLA2), S-5920/LY315920Na, in an experimental model of acute pancreatitis in rats. Combined intraductal injection of sodium taurocholate (5 mg/rat) and porcine pancreatic sPLA2-IB (300 μg/rat) caused severe hemorrhagic necrotizing pancreatitis resulting in high mortality, along with rapid increases of catalytic PLA2 and lipase activities in plasma and ascites and with gradual increases of plasma amylase and aspartate aminotransferase levels over 9 h after the pancreatitis. Prophylactic intravenous treatment with S-5920/LY315920Na significantly reduced mortality at 7 days, and strongly abrogated PLA2 activities in both plasma and ascites along with significant reduction of lipase activity, amylase, aspartate aminotransferase, and hemorrhage at 6 h. It also significantly reduced histological damage such as edema and parenchymal and fat necroses of the pancreatic tissue. This sPLA2 inhibitor could become an effective agent for the treatment of severe acute pancreatitis. Keywords:: phospholipase A2, pancreatitis, parenchymal necrosis, S-5920/LY315920Na